Pengaruh Kepemimpinan Transformasional terhadap Kinerja Karyawan di Era Digital - Siska Yustika (PUTRA JAWA PUBLISHER, 2025)
The primary objective of this research is to investigate how transformational leadership impacts the performance of employees during the digital age. In essence, transformational leadership is a type of leadership that has the capability to encourage, motivate, and enable employees by providing a clear vision and utilising effective communication. During the digital age, advancements in technology impact how work is done and require quick adjustments from both businesses and individuals. This research utilises a quantitative method by gathering information from a questionnaire answered by 150 technology sector workers. The findings indicate that transformational leadership plays a key role in enhancing employee performance, particularly in fostering innovation, teamwork, and the ability to adapt to technological advancements. As a result, this style of leadership is crucial in overcoming the obstacles presented by the digital age and improving overall organisational efficiency.